1984
DOI: 10.2307/2443371
|View full text |Cite
|
Sign up to set email alerts
|

Flower, Fruit and Seed Abortion in Tropical Forest Trees: Implications for the Evolution of Paternal and Maternal Reproductive Patterns

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
229
3
18

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(270 citation statements)
references
References 61 publications
(148 reference statements)
20
229
3
18
Order By: Relevance
“…There was a trend to greater seed production at the distal end of the pod. This was earlier reported in legumes by Bawa & Webb (1984). Linear non random seed set patterns with hardly any seed formation at the first basal ovule position were also found in pods of bee pollinated Lupinus nanus and Medicago sativa (Horowitz et al, 1976).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There was a trend to greater seed production at the distal end of the pod. This was earlier reported in legumes by Bawa & Webb (1984). Linear non random seed set patterns with hardly any seed formation at the first basal ovule position were also found in pods of bee pollinated Lupinus nanus and Medicago sativa (Horowitz et al, 1976).…”
Section: Discussionsupporting
confidence: 84%
“…Pod production under natural conditions is relatively high, especially when compared with studies on other legumes in which only 10% and sometimes even less than 1% of the flowers produce a pod (Stephenson, 1981;Bawa & Webb, 1984). Flower and pod abortion is common in shrubs and trees with hermaphrodite flowers and need not be attributed to the lack of compatible pollen or a limitation of resources.…”
Section: Discussionmentioning
confidence: 97%
“…The abortion of young fruits is common due to self-incompatibility when self-pollination occurs (Bawa & Webb 1984). This could be the case in monoiceous species such as B. rubesecens when flower production is high; under such conditions pollinators are easily satiated in a single tree, which increases the chances of self-pollination.…”
Section: Availability Of Seed Sources Fecundity and Phenological Varmentioning
confidence: 99%
“…Sometimes ovules fail to produce mature seeds because pollination/fertilization has not occurred or as a result of external factors such as seed predation, but often fertilized ovules abort prior to maturation (Lee and Bazzaz 1986;Lee 1988;Nakamura 1986). Nakamura (1988) noted that, for many species, seed abortion is the greatest cause of mortality in the sporophytes' life cycle, and several authors using various lines of reasoning have speculated that the overproduction of ovules followed by non-random seed abortion on the basis of progeny vigor could increase the average vigor of the seed crop (Bawa and Webb 1984;Charnov 1979;Stearns 1987;Westoby and Rice 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we (Rocha and Stephenson 1990) have shown that seed abortion in Phaseolus coccineus (Leguminosae), like that in many other species with linearly arranged ovules, is non-random with respect to the position of the ovule within the ovary (Halsten 1917;Bawa and Webb 1984;Harper and Wallace 1987;Horovitz et al 1976;Nakamura 1986). The three ovules at the stylar end of the fruit have a higher probability of maturation than the three ovules at the basal (peduncular) end of the fruit.…”
Section: Introductionmentioning
confidence: 99%